Semantic Analysis of English Polysemous Words - Umida Sultanova (Indonesian Journal Publisher, 2025)
The objective of this research is to analyze the phenomenon of polysemy in English by identifying its semantic mechanisms, cognitive origins, and practical implications. Using a qualitative semantic analysis approach, the study examines metaphor, metonymy, generalization, and specialization as key processes that lead to the development of multiple meanings for a single word. Examples such as “run,” “head,” and “light” are analyzed to illustrate semantic expansion. The findings suggest that polysemy not only reflects the dynamic evolution of language but also poses challenges for language learners and lexicographers. Understanding polysemy is essential for improving language comprehension, translation accuracy, and dictionary design